Compreensões sobre o desenvolvimento da unidade temática lazer em uma turma do ensino fundamental de uma escola pública - Salvador, Guilherme (Universidade Federal de São Carlos, 2023)
The present study had as its starting point the thematization of leisure in Physical Education classes, especially with regard to the understanding of the right to leisure enshrined in the Federal Constitution, paying attention to sociocultural and ideological aspects. The objective of this research was to describe and analyze the development of the Leisure theme in Physical Education classes for a class of elementary school students in a public school located in the urban periphery of the city of São Paulo. For this, an intervention project was carried out with the leisure theme, containing 8 classes of 45 minutes each, with students enrolled in the 8th grade B of the Municipal Bacharel Mário Moura e Albuquerque school, between August and November 2022. Among the contents, the cultural interests of leisure, leisure within the school, and the game “leisureified dodgeball” were addressed, proposed to problematize characteristics present in the context of leisure. Data collection was carried out during the thematic unit, with moments of filming, photographic records, and notes to assist in the construction of Field Notes. For data analysis, we used the development of Coding Categories, based on the identification of Data Units. In light of the data collected and analyzed, the results made it possible to elaborate two categories and five subcategories, namely: Category A) Leisure in the context of a thematic unit; Subcategory 1 - Absence of leisure conceptions in the reality of the students; Subcategory 2 - School culture, diversity of leisure, and student diversity; Subcategory 3 - School as a place of reproduction of leisure values in society; Category B) Impact of the thematic unit on leisure; Subcategory 4 - Leisure as an individual universe of the human being; 5 - School as a place of emancipation through leisure. The results indicated limited understandings of the students and little curricular stimulus for pedagogical approaches to leisure, as well as a lack of actions focused on leisure in school and in the community. However, it allowed for good impressions about the thematization of leisure among students, especially when issues related to freedom and control in various daily activities experienced by them and their ways of understanding leisure were addressed. To overcome the scarcity of pedagogical approaches to leisure in the school environment, it is necessary that the theme be collectively reflected upon and that adequate training be provided to work with this important social right.
Understandings about the development of the thematic unit leisure in a class of elementary school students in a public school
Keywords: Educação física escolar; School physical education; Lazer; Leisure; Ensino; Teaching; CIENCIAS DA SAUDE::EDUCACAO FISICA